Challenges confronting the prevention of mother to child transmission of HIV/AIDS in Offa Local Government Area, Kwara-State (2014)
This study investigated the challenges confronting the prevention of mothers-to-child transmission of HIV/AIDS in Offa Local Government Area of Kwara State, Nigeria. The transmission of HIV/AIDS from mother-to-child has been a rampant phenomenon in Offa L.G.A. A descriptive research of survey type was used, the population for the study covered all the health workers in Offa Local Government Area, 145 respondents were sampled for the study. Three research questions were raised and three hypotheses were generated which were tested at 0.05 alpha level of significance. The research instrument used for the study was a questionnaire which was validated and tested for reliability. A reliability co-efficient of 0.76r was obtained; using pearson product moment correlation. The instrument was administered by the researchers and some trained research assistant. A descriptive statistic of frequency count and percentage was used for the personal data while the inferential statistic of chi-square was used at 0.05 alpha level of significance to test the hypotheses set for the study. The null hypotheses set were rejected, the findings of this study revealed that challenges such as non-disclosure of HIV/AIDS status, inadequate staff training and inavailability of antiretroviral drugs are parts of the major challenges militating against the proper implementation of prevention of mother to child transmission of HIV/AIDS. It was recommended that there should be adequate staff training to improve their knowledge on the transmission of HIV/AIDS especially in the area of vertical transmission with appropriate treatment. Also, antiretroviral drugs should be available in Health centres and hospitals for the treatment of HIV/AIDS positive mothers and prevention of vertical transmission of the infection, lastly HIV status of pregnant women should be known in order to commence treatment immediately.